Early Life Stress, Coping, and Cardiovascular Reactivity to Acute Social Stress. Issue 2 (27th February 2023) - Mrug, Sylvie; Pollock, Jennifer S.; Pollock, David M.; Seifert, Michael E.; Johnson, Kim A.; Knight, David C.
ABSTRACT: Objective: Early life stress (ELS) occurring during childhood and adolescence is an established risk factor for later cardiovascular disease and dysregulated reactivity to acute social stress. This study examined whether ELS associations with baseline cardiovascular functioning, cardiovascular stress reactivity and recovery, and emotional stress reactivity vary across levels of emotion-oriented, task-oriented, and avoidant coping styles. Methods: The sample included 1027 adolescents and young adults (mean age = 19.29 years; 50% female; 64% Black, 34% non-Hispanic White) who reported on their ELS exposure and coping styles. Participants completed a standardized acute social stress test (the Trier Social Stress Test [TSST]), with heart rate (HR) and blood pressure (BP) measured before, during, and after the TSST. Self-reports of negative emotions during the TSST indexed emotional stress reactivity. Results: Multiple regression models adjusting for demographic factors and body mass index showed that ELS was associated with lower HR stress reactivity, avoidant coping was related to lower systolic BP and diastolic BP during stress and lower systolic BP during recovery, and higher emotion-oriented coping and lower task-oriented coping predicted greater emotional stress reactivity. A consistent pattern emerged where emotion-oriented coping amplified the associations between ELS and maladaptive stress responses (blunted cardiovascular stress reactivity and recovery; enhanced emotional stress reactivity), whereas lower levels of emotion-oriented coping were associated with resilient profiles among those who experienced ELS (lower resting HR, lower emotional stress reactivity, average HR and BP stress reactivity and recovery). However, low levels of emotion-oriented coping also conferred a risk of higher BP during recovery for those with high levels of ELS. Conclusions: These results suggest that low to moderate levels of emotion-oriented coping promote optimal cardiovascular and emotional reactivity to acute stress among individuals exposed to ELS.